A laboratory and field investigation of aerobic biodegradation of sulfolane in groundwater. Issue 10 (14th July 2021) - Mulder, D'Arcy W; Yu, Linlong; Achari, Gopal
Abstract: BACKGROUND: Sulfolane has recently emerged as a contaminant of concern in and around oil and gas processing sites in North America and elsewhere. In this research, a comprehensive laboratory study was conducted to investigate the importance of several factors (nutrient levels, aeration methods and inoculants) involved in aerobic biodegradation of sulfolane in groundwater. The aerobic biodegradation of sulfolane was also evaluated under field conditions, which can provide useful information for future field application. RESULTS: A lag period of 40–141 h and a zero‐order rate of 0.6–6 mg L −1  h −1 for sulfolane degradation were observed under different laboratory conditions. The aerobic biodegradation rates observed in the field in Alberta, Canada were 4–6 mg L −1  day −1 . A C:N:P ratio of 100:5:1 was determined to be suitable for aerobic degradation of sulfolane. The introduction of sediments from sulfolane‐contaminated sites can shorten the lag period from 141 to 74 h. CONCLUSIONS: Sulfolane can be effectively degraded in groundwater using aerobic biodegradation in both laboratory and field conditions. A negative correlation was obtained between adenosine triphosphate and sulfolane concentration when it started to degrade. © 2021 Society of Chemical Industry (SCI).